Etude de la simplification et standardisation du protocole de pesées chez les ovins à viande - Ben Gara A.; Rouissi H.; Jurado J.J.; Bodin L.; Gabiña D.; Boujenane I.; Mavrogenis A.P.; Djemali M.; Serradilla J.M. (Data collection and definition of objectives in sheep and goat breeding programmes: New prospects, 1997)
Growth recording systems of Barbarin lambs in Tunisia (11,449 lambs), Timahdit in Morocco (19,065 lambs), Merinos in Spain (8,800 lambs), Chios (10,019 lambs) and Awassi (1,619 lambs) in Cyprus have been analysed. To simplify current recording systems, some alternatives have been proposed. The comparison of different alternatives was based on the average difference and the standard deviation of the individual differences for each trait. The effect of simplifications on the genetic progress was verified by modifications in estimated genetic parameters and correlations among breeding values. For the Barbarine breed, a recording system based on 5 consecutive rounds might be adopted. A similar system would be appropriate for the Merino breed if the 90-day weight was not the breeding objective. For the Timahdit breed, the reduction to almost 4 months of the length of lambing season for lambs forming the selection basis would be advised. On the other hand, the study was limited to the estimation of genetic parameters for the Chios and Awassi breeds..
Meeting of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats and Subnetwork on Animal Resources, 9-11 Mar 1997, Toulouse (France)